ChemInform Abstract: A Theoretically‐Guided Optimization of a New Family of Modular P, S‐Ligands for Iridium‐Catalyzed Hydrogenation of Minimally Functionalized Olefins. Issue 11 (March 2015) - Margalef, Jessica; Caldentey, Xisco; Karlsson, Erik A.; Coll, Merce; Mazuela, Javier; Pamies, Oscar; Dieguez, Montserrat; Pericas, Miquel A.
Abstract A library of novel modular iridium complexes derived from thioether‐phosphite/phosphinite ligands are synthesized and evaluated in the asymmetric hydrogenation of minimally functionalized olefins.